Survey of lifestyle and its relationship with health value of mid-aged women referring to comprehensive health centers of Isfahan in 2016 - Zahra Sadat Mousavi; Soheila Ehsanpour; Ashraf Kazemi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Health needs a lifestyle upgrade. Lifestyle is important because it affects the quality of life and the diseases' prevention. This study aimed to investigate the lifestyle and its relationship with health-care value of mid-aged women. Methods: This descriptive-analytic study was conducted on 287 middle-aged women in Isfahan in 2016. Samples were randomly selected among the centers as well as from those referring to comprehensive urban health centers. Walker's Health-Promoting Lifestyle Profile II and a researcher-made health-care value questionnaire were provided to mid-aged women. Data were analyzed using descriptive statistics, Pearson's correlation coefficient tests, and multiple linear regression (MLR) analysis. Results: The average health value score in women was 59.6 and the total lifestyle score was 57.9 out of 100, which is in the semi-desirable range. The highest score among the lifestyle domains was related to the interpersonal relationship (67.6) and the lowest score was related to physical activity (39.4). Pearson's correlation coefficient showed that there is a direct relation between the health value score and the total score of lifestyle and all its domains (P < 0.001). MLR model showed that the areas of responsibility (P < 0.001), interpersonal relationships (P < 0.001), and physical activity (P = 0.01) have the highest predictive value for the health value score among the different domains of lifestyle score. Conclusion: Lifestyle and health value of mid-aged women in Isfahan are in the semi-desirable range and lifestyle has a direct relationship with health value. Therefore, lifestyle enhancement can enhance the health value and take steps to improve health in the community.